Experimental platform tests for setting performances of distance protection installed in Biskra-Batna of the Algerian transmission line - Yassine Khelil; Belkacem Mahdad; Abdelhak Tobbeche (International Journal of Applied Power Engineering (IJAPE), 2021)
The modern power system is equipped with protection system based on advanced technology through the use of digital multifunction relay, control system and intelligent selectivity, whose purpose is to ensure maximum security and service continuity of protection relay in the presence of various fault currents. Distance protection is an important protection required in high voltage transmission lines. In this paper, experimental platform tests have been performed and proposed for setting and evaluation the performances of distance protection named Micom P442 installed in Biskra-Batna of the Algerian transmission power system. The performances of the distance protection have been evaluated under various short circuits. In this study, experimental result based single phase fault to ground is analysed and discussed. Experimental results based on the proposed platform tests in terms of precision in detecting faults at various locations and trigger times confirm the efficiency and particularity of the proposed experimental platform tests.